2023
DOI: 10.2147/ppa.s415593
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Self-Management of Peritoneal Dialysis Patients in Urumqi of Xinjiang of China: A Cross-Sectional Survey

Abstract: Purpose To explore the factors associated with self-management of Peritoneal Dialysis (PD) patients and methods of acquiring PD knowledge. Design Cross-sectional survey design. Setting Urumqi, Xinjiang, China. Patients 131 Chinese maintenance Peritoneal Dialysis (PD) patients. Methods This cross-sectional study was conducted from October 2019 to March 2020 in the First Affiliated Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…[8] Some studies have shown that expanding disease-related knowledge can help patients with cancer establish confidence and improve their quality of life. [9][10][11] In this study, we strengthened continuous nursing through the "Internet Plus" system, including via WeChat groups and educational videos (in both Mandarin and the regional local dialects), and set up a special interventional nursing team. The health education and nursing training procedures for patients and their families regarding bladder cancer were enhanced through this approach, and tube nursing guidance was also provided for some patients who required chronic indwelling drainage or urinary tubes.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Some studies have shown that expanding disease-related knowledge can help patients with cancer establish confidence and improve their quality of life. [9][10][11] In this study, we strengthened continuous nursing through the "Internet Plus" system, including via WeChat groups and educational videos (in both Mandarin and the regional local dialects), and set up a special interventional nursing team. The health education and nursing training procedures for patients and their families regarding bladder cancer were enhanced through this approach, and tube nursing guidance was also provided for some patients who required chronic indwelling drainage or urinary tubes.…”
Section: Discussionmentioning
confidence: 99%